PENGARUH KUALITAS MAKANAN, KUALITAS PELAYANAN DAN KUALITAS LINGKUNGAN FISIK TERHADAP NIAT PERILAKU PEMBELIAN ULANG PELANGGAN (PADA PELANGGAN RESTOTAN SOTO LAMONGAN CAK HAR DI SURABAYA) - VAZHAR SETYA PUTRA (Jurnal Manajerial, 2018)
The purpose of this study was to determine the effect of food quality, service quality and physical environmental quality on customer buying behavior intentions (at customer restotan soto lamongan cak har in Surabaya). The sample uses a non-probability sampling method with a purposive technique that is by selecting respondents who are subscribed to the soto lamongan cak har restaurant in Surabaya. Data analysis techniques use multiple linear regression. The results of multiple linear regression analysis proved that the quality of food, service quality and physical environment quality proved to have a significant partial effect on customer repurchase behavior intention in Soto Lamongan cak har Surabaya